Combination of Weed Solution and Concentrate to Control Thrips sp and Aphis sp Pests in Chrysanthemum Plants - Andriani, A. A. S. P. R.; Arjana, I Gusti Made; Mahardika, Ida Bagus Komang (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Chrysanthemum (Chrysanthemum sp.) is one of the ornamental flower commodities that has high economic value. A significant problem for farmers in cultivating chrysanthemums is the presence of Thrips sp. and Aphis sp. pests. Thrips sp. is an insect pest that attacks plants, while Aphis sp. is an aphid pest. Both of these pests can cause significant losses by directly damaging leaves, reducing plant growth, and affecting flower quality. Conventional pest control methods, such as the use of chemical insecticides, can have negative impacts on the environment and human health, and can cause pest resistance to these chemicals. Several types of weeds, such as Echinochloa crus-galli, Panicum repens, Euphorbia hirta, and Ageratum conyzoides, are known to contain active compounds with insecticidal properties, including tannin content. The purpose of this study was to determine the effect of the combination of weed solution and its concentration in controlling Thrips sp. and Aphis sp. pests on chrysanthemums. The research design employed a Factorial Randomized Block Design, conducted in both the field and a greenhouse, with two factors: Factor I, which was a Combination of weed solutions, and Factor II, which was the concentration of the weed solution. The production data obtained were analyzed using Analysis of Variance, followed by the BNT or Duncan 5% distance test. The quality data of chrysanthemum flowers were compared with SNI 01-4478-1988. The variables observed included the intensity of pest attacks, stem diameter, leaf diameter, plant height, and the fresh weight of the plants. Contribution to Sustainable Development Goals (SDGs):SDG 3:-Good Health and Well-beingSDG 12: Responsible Consumption and ProductionSDG 15- Life on Land